DETERMINANTS OF FINANCIAL INCLUSION: TURKEY AND WORLD APPLICATION (Third Sector Social Economic Review, 2020)
The purpose of this study is to determine the individual factors affecting the financial inclusion for economies in the different income levels across the globe and for Turkey. In addition, the individual factors affecting the barriers to the financial inclusion, the borrowing preferences of individuals, the reasons for savings, the use of bank and credit cards and the use of loans for real estate are also investigated in the study. By using the World Bank 2017 Global Findex database, the effect of gender, age, income and education on the financial inclusion is analyzed with probit regression analysis. The results of the study revealed that individual factors have important effects on the indicators of financial inclusion. In addition, it is concluded that individual factors have an impact on the reasons that prevent account ownership in financial institutions, the borrowing preferences of individuals, their reasons for savings, their bank and credit card ownership, and their use of credit for real estate.
Keywords: Financial Inclusion; Individual Factors; Turkey